IMPLIKASI HUKUM TIDAK DILAKSANAKANNYA PUTUSAN MAHKAMAH KONSTITUSI DALAM PERKARA PENGUJIAN UNDANG-UNDANG - Andre Suryadinata; Toendjoeng Herning Sitaboeana (Fakultas Hukum Universitas Tarumanagara, 2019)
The Constitutional Court is one of the branches of judicial power that has authority to adjudicate at the first and last level whose decision is final to test the law against the Constitution as regulated in Article 24C paragraph (1) of the 1945 Constitution. The final nature of decision of the constitutional court is binding on the entire community since it was said in the Open Plenary Session. Therefore, decision of constitutional court that invalidates the validity of a law must be followed up by legislators in the cumulative list open to the national legislation program. But in practice there are 2 (two) decisions that have not been followed up, namely Constitutional Court Decision Number 31 / PUU-XI / 2013 and Constitutional Court Decision Number 30 / PUU-XVI / 2018. Based on this description, it will be examined regarding the legal implications of not implementing the Constitutional Court Decision in case of judicial review? The author examines the problem using the method of normative legal research with the statutory approach. From the results of this study, it was found that the non-follow-up of the two decisions had violated the principle of rule of law in concept of the rule of law, and caused the loss of the decision-making power, and was a form of neglect of principle of legal awareness. So it is necessary to make changes in stages of the Constitutional Court Law and the House of Representatives' Regulations on Rules of Procedure.